Chlorpheniramine Potentiates the Analgesic Effect in Migraine of Usual Caffeine, Acetaminophen, and Acetylsalicylic Acid Combination - Voicu, Victor A.; Mircioiu, Ion; Sandulovici, Roxana; Mircioiu, Constantin; Plesa, Cristina; Velescu, Bruno S.; Anuta, Valentina (Frontiers in Pharmacology, 2017)
Previous studies indicated that addition of the antihistaminic chlorpheniramine to the usual combination of acetylsalicylic acid, acetaminophen and caffeine further increases their synergism both in terms of anti-inflammatory and analgesic effect. The present non-interventional study tested the superiority of two Algopirin® tablets, containing a total of 250 mg acetylsalicylic acid (ASA), 150 mg acetaminophen (paracetamol, PAR), 30 mg caffeine (CAF) and 4 mg chlorpheniramine (CLF) versus a combination containing 250 mg ASA, 250 mg PAR and 65 mg CAF recognized as “safe and effective” by FDA in treating migraine. Patients evaluated their pain intensity on the Visual Analog Scale – VAS(PI) before and 30, 60, 120, 180 and 240 min after drug intake. Interpretation of the pain curves as “survival pain curves” was considered as a method for direct comparison of the pain curves. This interpretation permitted the application of Cox methods for comparison of pain hazards. The results of the applied statistical tests were similar and pointed out that Algopirin® was more efficient in spite of much smaller doses of PAR and CAF. Consequently, the addition of CLF permitted decreasing of ASA, PAR and CAF doses as well as their potential side effects, without a loss of analgesic effect.